2005
DOI: 10.1063/1.1862624
|View full text |Cite
|
Sign up to set email alerts
|

Methodological problems in pressure profile calculations for lipid bilayers

Abstract: From molecular dynamics simulations of a dipalmitoyl-phosphatidyl-choline (DPPC) lipid bilayer in the liquid crystalline phase, pressure profiles through the bilayer are calculated by different methods. These profiles allow us to address two central and unresolved problems in pressure profile calculations: The first problem is that the pressure profile is not uniquely defined since the expression for the local pressure involves an arbitrary choice of an integration contour. We have investigated two different c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

11
170
0
2

Year Published

2008
2008
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 126 publications
(183 citation statements)
references
References 39 publications
11
170
0
2
Order By: Relevance
“…Note that, because the contribution in reciprocal space is not pairwise additive, it is not possible to use an Irving-Kirkwood formulation either for the Ewald sum, or for its mesh-based approximations. 11 We now proceed to extending the reciprocal space contribution to mesh-based algorithms, by noting that Eq. (9) is, for µ = ν, the discrete inverse Fourier transform of the complex function S(m)f (m 2 )g µν (m), evaluated at the particles' positions, and scaled by the factor q i .…”
Section: The Reciprocal Space Contributionmentioning
confidence: 99%
See 3 more Smart Citations
“…Note that, because the contribution in reciprocal space is not pairwise additive, it is not possible to use an Irving-Kirkwood formulation either for the Ewald sum, or for its mesh-based approximations. 11 We now proceed to extending the reciprocal space contribution to mesh-based algorithms, by noting that Eq. (9) is, for µ = ν, the discrete inverse Fourier transform of the complex function S(m)f (m 2 )g µν (m), evaluated at the particles' positions, and scaled by the factor q i .…”
Section: The Reciprocal Space Contributionmentioning
confidence: 99%
“…20 ). Sonne and collaborators 11 showed that the pressure profile calculated using the Irving-Kirkwood approach and a cutoff radius of 2 nm is qualitatively similar to the one calculated using the Harasima path with long-range electrostatic contributions, although with an indetermination of roughly 100 to 200 bar, which makes it only a qualitative test.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Many simulated systems have inhomogeneity only in two dimensions (2D) such as defect nucleation in bulk and two-dimensional crystals, bio molecular assemblies such as lipid bilayers and membrane proteins, as well as thin film evaporation and heat transfer, and thus only require 2D pressure distribution. However, current literature on local pressure estimation is based on 3D [3] or 1D [4][5][6] pressure estimation. The 2D pressure distribution is obtained by averaging over the 3D pressure data, and is extremely computationally expensive [7] as it involves a 3D convolution.…”
Section: Introductionmentioning
confidence: 99%